2005
DOI: 10.1074/jbc.m410213200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and Contraction Stimulate Exocytosis, but Increased AMP-activated Protein Kinase Activity Resulting from Oxidative Metabolism Stress Slows Endocytosis of GLUT4 in Cardiomyocytes

Abstract: Stimulations of glucose transport produced by insulin action, contraction, or through a change in cell energy status are mediated by separate signaling pathways. These are the wortmannin-sensitive phosphatidylinositol 3-kinase pathway leading to the intermediate Akt and the wortmannin-insensitive AMP-activated protein kinase (AMPK) pathway. Electrical stimulation of cardiomyocytes produced a rapid, insulin-like, wortmannin-sensitive stimulation of glucose transport activity, but this occurred without extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 54 publications
10
84
1
Order By: Relevance
“…CDE is essential for activating signaling downstream of EGF and TGF␤ because the signaling complex for these hormones is assembled on the surface of the CDE endosome after endocytosis. In contrast, signaling via insulin is initiated by receptor on the cell surface, and CDE-mediated endocytosis of insulin-IR is the first step in shutting off signaling (54). Thus, lack of endocytosis causes a greater dwell-time of the insulin-IR complex on the plasma membrane surface, translating into greater insulin sensitivity of the RLIP76 Ϫ/Ϫ mice (42), and signaling pathways downstream of insulin including AKT and AMPK are activated at baseline in RLIP76 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…CDE is essential for activating signaling downstream of EGF and TGF␤ because the signaling complex for these hormones is assembled on the surface of the CDE endosome after endocytosis. In contrast, signaling via insulin is initiated by receptor on the cell surface, and CDE-mediated endocytosis of insulin-IR is the first step in shutting off signaling (54). Thus, lack of endocytosis causes a greater dwell-time of the insulin-IR complex on the plasma membrane surface, translating into greater insulin sensitivity of the RLIP76 Ϫ/Ϫ mice (42), and signaling pathways downstream of insulin including AKT and AMPK are activated at baseline in RLIP76 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbed glucose would be an easily metabolized energy source to remodel the actin cytoskeleton in preparation for the increased glomerular filtration load the meal would produce. A similar adaptive process for cellular remodelling occurs in cardiac and skeletal muscle where glucose is absorbed in response to contractility (40).…”
Section: Diabetes Vol 56 April 2007mentioning
confidence: 99%
“…The effects of short-term exercise may be related to increased contractile activity and to the associated signalling. However, in experimental situations, short-term heart contractile activity appears to be linked to incompletely characterised signalling steps that are partially separate and distinct from AMPK signalling (Kolter et al, 1992;Yang and Holman, 2004). Similar considerations apply to exercise and contractionregulated signalling in skeletal muscle (reviewed by Sakamoto and Goodyear, 2002;Sakamoto et al, 2003;Sakamoto and Holman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that, although the routes of GLUT4 vesicle trafficking are similar, the details of the kinetics of trafficking may differ. We have previously reported that whereas insulin action and contractioninduced stimulation lead to increases in the exocytosis of GLUT4 in cardiomyocytes, stimulation of the AMPK pathway by means of hypoxia, mitochondrial inhibition (Yang and Holman, 2005) or metformin action (Yang and Holman, 2006) lead to inhibition of endocytosis. These differences in the kinetics of trafficking may lead to a lower level of exposure of the HA-epitope relative to the GFP in the case of reduced endocytosis.…”
Section: Translocation Of Glut4 To Sarcolemma and Transverse-tubule Mmentioning
confidence: 99%